A qualidade e o modelo common assessment framework: O caso dos Serviços Académicos da Universidade de Évora - Nogueiro, Teresa Paula Ramalho Serra Bugalho (2016)
Uma das condições que mais influencia a competitividade entre instituições de ensino é a Qualidade. Sendo a sociedade cada vez mais exigente, é necessário medir e avaliá-la. A utilização de uma ferramenta de autoavaliação, desenvolvida ao nível da União Europeia, a Common Assessment Framework (CAF), que teve como modelo de origem o European Foundation for Quality Management (EFQM), veio permitir a medição da qualidade dos serviços prestados na administração pública. Este estudo apresenta os diversos aspectos referentes à temática da qualidade, o modelo CAF e os principais resultados obtidos num inquérito por questionário, junto dos alunos, colaboradores internos e gestores dos Serviços Académicos da Universidade de Évora, com o objectivo de avaliar o grau de satisfação com a qualidade do serviço prestado, o desempenho de todas as partes interessadas e, consequentemente, a sustentabilidade desse serviço. Desses resultados retiraram-se alguns pontos fortes, enunciaram-se diversos pontos fracos e evidenciaram-se sugestões de melhoria para o serviço em estudo. Neste sentido, este trabalho serviu de diagnóstico e apresenta uma ferramenta que permite aos Serviços académicos da Universidade de Évora conhecerem-se melhor e poderem mover-se no caminho da qualidade. ABSTRACT: One of the conditions that most influences the competitiveness among institutions of education is quality. As society increasingly demanding in terms of professional skills, it is necessary to measure and assess the quality of education, through continuous improvement to achieve excellence. Currently, the quality must be measured and seen as a competitive advantage. The use of a tool for self-evaluation of the quality, developed at EU level, the Common Assessment Framework (CAF) that has had its origin on European Foundation for Quality Management (EFQM), carne allow the measurement of quality of services provided to the clients, based on an internal guidance for quality in the organization and on the adoption of quality ratings as a routine in their work. This study presents the various aspects relating to the issue of quality and the Common Assessment Framework (CAF) and presents the main results obtained through a survey by questionnaire. These questionnaires were applied to the students, staff and internal managers from the Academic Services of the University of Évora with the aim of assessing the grade of satisfaction with the quality of the services provided, the performance of all interested parties and therefore the sustainability of this service in this institution of higher education. As results obtained on this research there are some strengths, several weaknesses and suggestions for improvement that can benefit the service under study. This work can be used as a diagnosis and gives a tool that allows Academic Services of the University of Évora know themselves better and to be able to move on the path of quality.